2018
DOI: 10.1016/j.cpme.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Surface treatment with non-thermal humid argon plasma as a treatment for allergic contact dermatitis in a mouse model

Abstract: Cold plasma generated at atmospheric pressure has attracted intense interest in biomedical applications, particularly as an antimicrobial treatment. Here we report the therapeutic effect of humidified cold argon plasma on allergic contact dermatitis (ACD) in a mouse model. Treatment was carried out with different gas compositions: argon gas containing small amounts of either N2, O2, or H2O. The best effect was obtained using humid plasma (H2O addition), where the ACD symptoms decreased after one or two 1-min p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Studies on skin inflammatory diseases such as allergic contact dermatitis and atopic dermatitis have shown anti-inflammatory effects of non-thermal plasma [134][135][136]. These effects have also been observed in oral studies.…”
Section: Anti-inflammatory Properties and Wound Healingmentioning
confidence: 89%
“…Studies on skin inflammatory diseases such as allergic contact dermatitis and atopic dermatitis have shown anti-inflammatory effects of non-thermal plasma [134][135][136]. These effects have also been observed in oral studies.…”
Section: Anti-inflammatory Properties and Wound Healingmentioning
confidence: 89%
“…Recently, NTAPP has been studied for its beneficial effects such as proliferation, angiogenesis, maintaining the stem cell characteristics, and promoting wound healing 8 12 , 30 . Furthermore, therapeutic evidences in pre-clinical models of inflammatory skin disease have been also reported 31 33 . However, the effect of NTAPP on hair growth or regeneration still remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, using a mouse model of allergic contact dermatitis (ACD), Xiong et al. found that humidified CAP is better than oxygen or nitrogen plasma when treating mild and severe ACD ( 62 ). This was mainly because active species delivered by water-containing argon plasma became adhesive to the dry skin of ACD leading to good penetration of ROS.…”
Section: Treatment Of Skin Disease Using Capmentioning
confidence: 99%